Xanthine oxidase inhibitory activity by flavonoids from Chrysanthemum morifolium: in vitro and in silico insights - Tey, Zi Tong; Loh, Khye Er; Tan, Siow-Ping; Yuan, Chongjun; Tejo, Bimo Ario; Ismail, Intan Safinar; Nafiah, Mohd Azlan (Elsevier, 2024)
2-(3’,4’-dihydroxyphenyl)-3,6,7,8-tetramethoxy-4H-chromen-4-one (3), a new flavonoid was isolated from the ethyl acetate fraction of Chrysanthemum morifolium Ramat. dried flowers, while 4′,5-dihydroxy-3,3′,7,8-tetramethoxy-flavone (1) and casticine (5) were isolated from this plant for the first time, as well as two known flavonoids, eriodictyol-7-O-glucoside (2) and luteolin (4). Their structures were investigated over a broad spatial scale using chromatographic and spectroscopic techniques (NMR, FTIR, UV and HR-ESI-MS). Compound 4 showed the highest XO inhibition and the most favorable interaction with XO in molecular docking analysis. Compound 2, 3 and 4 demonstrated stable interactions with catalytically important residues in xanthine oxidase via molecular dynamic analysis.